Anaximander of Miletus: the Axiological Expression of Justice. - Dan Paranyuk, Serhiy Melenko (Журнал східноєвропейського права, 2017)
The phenomenon of justice, as an axiologically indispensable feature of society, has always drawn attention of numerous generations of thinkers, who tried to reveal the most topical ontological needs of humanity in their works. However, in the context of the issue under discussion, it is necessary to determine the direct identifying features of the phenomenon under studies in order to give a definition of the notion of “justice” as an ontological category. In different periods of human existence, its most prominent representatives distinguished a range of features that might be regarded as identifying ones, since they expressed various wants of the society in the most universal and complete way. Among the diversity of the above-mentioned features, they differentiate a particular group that has never lost its importance, which, in its turn, makes it possible to identify the phenomenon of justice in any evolutionary period of social being. It is worth mentioning that the philosophers, who have been working on the issue under investigation at different times, did not always manage to express their gnoseological judgments properly. Nevertheless, having carried out the etymological analysis of their works, we might claim that there existed certain similarity in their understanding of different problems. It also concerns determining the identifying features of justice, as one of the principal elements of both social and human being. Consequently, the understanding of the phenomenon of justice, as an axiological category, should begin with the analysis of the scientific heritage of one of the brightest representatives of the Milesian School of Philosophy – Anaximander of Miletus. The philosophical-legal research of his ideological concepts in the works of the thinkers of further generations, who - in the course of their own scientific search - came to the problem of defining justice, as an axiological dimension of social being, is also very important.
Keywords: Anaximander of Miletus, apeiron, justice, divine manifestation of justice, Immanuel Kant, categorical imperative, moral law, “moral right”.